2002
DOI: 10.2307/4003477
|View full text |Cite
|
Sign up to set email alerts
|

Clipping and Precipitation Influences on Locoweed Vigor, Mortality, and Toxicity

Abstract: White locoweed (Oxytropis sericea Nutt. in T&G) is widespread throughout the short-grass prairies and mountain grasslands and causes chronic poisoning of cattle, sheep, and horses. The objective of this study was to determine the effect of clipping (simulated grazing) on vigor, mortality and toxic alkaloid concentration of white locoweed. One hundred locoweed plants were marked at each of 3 locations (New Mexico, Colorado, and Utah). Plants were stratified into 2 age/size classes: young/small < 5 stalks; older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is unclear if herbivory from insects or large ungulates influences swainsonine production. Swainsonine concentrations did not change in response to clipping used to simulate herbivory . There are no reports investigating the bioactivity of swainsonine against insects, fungi, or bacteria, with the exception of one preliminary study that suggested swainsonine had no effect on a native weevil herbivore of locoweeds .…”
Section: Influence Of Environmental Factors On Swainsonine Concentrat...mentioning
confidence: 95%
See 1 more Smart Citation
“…It is unclear if herbivory from insects or large ungulates influences swainsonine production. Swainsonine concentrations did not change in response to clipping used to simulate herbivory . There are no reports investigating the bioactivity of swainsonine against insects, fungi, or bacteria, with the exception of one preliminary study that suggested swainsonine had no effect on a native weevil herbivore of locoweeds .…”
Section: Influence Of Environmental Factors On Swainsonine Concentrat...mentioning
confidence: 95%
“…Swainsonine concentrations did not change in response to clipping used to simulate herbivory. 57 There are no reports investigating the bioactivity of swainsonine against insects, fungi, or bacteria, with the exception of one preliminary study that suggested swainsonine had no effect on a native weevil herbivore of locoweeds. 58 Lastly, swainsonine appears not to deter grazing by large ungulates, as animals take 2−3 weeks to show clinical signs and continue grazing locoweeds after becoming intoxicated.…”
Section: Swainsonine Concentrationsmentioning
confidence: 99%
“…Swainsonine concentrations do not change in respond to clipping used to simulate herbivory, nor does it deter grazing as animals become progressively more intoxicated (Ralphs et al . ; Pfister et al . ).…”
Section: Endophytes Of Locoweeds and Related Taxamentioning
confidence: 99%
“…The ability of O. sericea to form dinitrogen-fixing nodules has profound implications for understanding the ecology of this species. Oxytropis sericea is capable of competing with neighboring species by developing a long taproot to reach deeper moisture (Payne 1957), and by tolerating the loss of aboveground tissue (Ralphs et al 2002a). The competitiveness of O. sericea could also be enhanced by its ability to simultaneously associate with Embellisia sp.…”
Section: Discussionmentioning
confidence: 99%